The Impact of Exchange Rate on Balance of Payment and Economic Growth: An Empirical Evidence from Iraq for The Period of (2004-2019) Using the ARDL Model - Kanar Kamal Salih; Bzhar Nasradeen Majeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
One of the most significant tools that are used to guide the country’s economic policies in both sides of fiscal and monetary policy, is called exchange rate. The exchange rate plays a vital role in determining and directing any economics for the sake of competition via other macroeconomics variables, for instance; value of money, inflation, economic growth and the level of balance of payments. This research tries to investigate the impact of exchange rate in Iraq on Iraqi balance of payment in one side, and its economic growth on the other side for the period between 2004 and 2019. The research objectives are to examine the trends of Iraqi dinar exchange rate for the mentioned period above and how it affected on the balance of payment, as well as its impact on the economic growth via investigating the Iraqi real GDP. To do this, secondary data were collected through governmental and other official websites. Then, statistical and econometrics tools were used, such as normality, co-integration and ARDL in order to explore and reveal the outcome. The results demonstrated that, any increase in Iraqi exchange rate for the selected period had a positive and significant on BOP and economic growth in Iraq by 13.97% and 9.725 respectively.